Exploring the role of literary and media translation in forging new economic paradigms, environmental accountability, and health sovereignty - Alharahsheh, Abdelrauof Meqbel; Ismail, Sayed M; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
Sustainable development is argued and negotiated through narratives that travel across languages, media platforms, and educational systems. Economic “reform”, environmental “responsibility”, and public “health” are not neutral topics; they are storylines that define problems, distribute agency and blame, and authorize particular futures. Translation is one of the main infrastructures through which these storylines become portable and persuasive. Drawing on translation studies, critical discourse analysis, ecolinguistics, and critical language education, this article synthesizes interdisciplinary scholarship (2000-2024) to conceptualize literary and media translation as a form of narrative governance. The synthesis identifies recurrent translation mechanisms - lexical choice, metaphor shifts, omission and compression, paratextual framing, and audience-oriented recontextualization - that can either reproduce dominant paradigms (e.g., technocratic neoliberalism, consumerist environmentalism, biomedical paternalism) or enable counter-narratives oriented toward justice, dignity, and ecological care. Building on these insights, the article proposes a practical framework for critical EFL in which learners analyze and produce translations of literary and media texts to develop sustainability literacy, health communication competence, and civic agency. The framework integrates content-based instruction/CLIL, task-based learning, multimodal literacy, and critical reading, and it provides guidance for text selection, translation task design (e.g., subtitling, captioning, and translator’s notes), assessment, and teacher professional development. Finally, the paper maps the framework to the Sustainable Development Goals (SDGs) and discusses implications for national development agendas, including Vision 2030. Translation is repositioned not as a peripheral language exercise, but as a teachable site where learners practice how public meanings about economy, environment, and health are made - and how they might be remade.